Elektroniczne aspekty w organizacji i przebiegu zgromadzeń - Błażewski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The provisions of the Law on Assemblies Act regulate the use of electronic means of communication during the organization of a public assembly. The application of these means of communication takes place during the proceedings for the organization of an assembly and in connection with its conduct. The provisions allow the use of basic means of communication, such as e-mail and public websites so that electronic administration could be disseminated despite the high level of digital exclusion in society in Poland.
Keywords: public assembly; municipal authority; electronic means of communication